Analisis Karakteristik Peserta Didik Kelas VI SD : Kognitif, Psikomotorik, Moral, Sosial, dan Spiritual Dalam Pembelajaran - Ramadhan Lubis; Khairunnisa Khairunnisa; Army Fahita Harahap; Buti Sarma; Azmi Oktari Harahap (Lembaga Pengembangan Kinerja Dosen, 2026)
At the age range of 11–12 years, children enter the final phase of primary school which is marked by rapid development in various aspects, including cognitive, psychomotor, social, and moral, all of which are interrelated in the educational process. The development of elementary school-age children is the main foundation for the formation of personality, intelligence, and social-moral skills in the future. This study aims to analyze and describe the developmental analysis of aspects (cognitive, psychomotor, social, and moral) in children aged 11–12 years. This study uses a qualitative and descriptive approach, where data is collected through observation, interviews and documentation to understand behavior in depth. The results of the case study on the subject of Syifa Khairunnisa show that the development of these four aspects is well internalized in daily life. Syifa's cognitive development can be seen from her ability to understand material through repetition, awareness to adjust the way of learning when difficult, and the ability to explain lessons to friends in simple language. Psychomotor development is seen in good coordination of movements (e.g. in sports), fine motor skills, and self-control. In the aspect of Social Development, Syifa shows the ability to interact positively, work together, and choose peaceful ways to resolve differences of opinion. Lastly, Syifa's moral development is reflected in the attitude of caring, honesty, responsibility, obedience to school regulations, and the practice of religious values. Overall, this case study confirms that the development of children at the end of primary school is a holistic process that requires integrated support from the school environment and family.